2015
DOI: 10.1007/s11356-015-4658-5
|View full text |Cite
|
Sign up to set email alerts
|

Lycopersicon esculentum under low temperature stress: an approach toward enhanced antioxidants and yield

Abstract: Brassinosteroids (BRs) have been implicated to overcome various abiotic stresses, and low temperature stress poses a serious threat to productivity of various horticultural crops like tomato. Therefore, a study was conducted to unravel the possible role of BRs in conferring alleviation to low temperature stress in Lycopersicon esculentum. Twenty-day-old seedlings of tomato var. S-22 (chilling tolerant) and PKM-1 (chilling sensitive) were sown in earthen pots, and at 40 days stage of growth, plants were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Under water stress conditions, plant growth regulator including BRs and ABA significantly improved chlorophyll content and increased water potential in soybean ( Zhang M. et al, 2004 ). Khan et al (2015) reported that application of BRs led to considerable improvements in plant tolerance against chilling stress in terms of plant growth, photosynthesis and antioxidant system in tomato plants. Reguera et al (2013) stated that drought tolerance in rice was concomitant with the accumulation of Cks.…”
Section: Management Strategiesmentioning
confidence: 99%
“…Under water stress conditions, plant growth regulator including BRs and ABA significantly improved chlorophyll content and increased water potential in soybean ( Zhang M. et al, 2004 ). Khan et al (2015) reported that application of BRs led to considerable improvements in plant tolerance against chilling stress in terms of plant growth, photosynthesis and antioxidant system in tomato plants. Reguera et al (2013) stated that drought tolerance in rice was concomitant with the accumulation of Cks.…”
Section: Management Strategiesmentioning
confidence: 99%
“…The growth biomarkers [shoot and root length, shoot and root fresh (FM) and dry mass (DM)] were determined by the method followed by Khan et al (2015).…”
Section: Determination Of Growth Biomarkers and Leaf Areamentioning
confidence: 99%
“…The activities of various enzymes such as catalase (CAT, 1.11.1.6), peroxidase (POX, 1.11.1.7), superoxide dismutase (SOD, 1.15.1.1) and contents of proline were analysed as described in our previous study (Khan et al 2015). The activity of enzyme was expressed on the basis of fresh mass in the form nM(H 2 O 2 ) decomposed g -1 (FM) for CAT, U g -1 (FM) for POX, U g -1 (FM) for SOD and mg g -1 (FM) for protein.…”
Section: Determination Of Leaf Gas-exchange Traitsmentioning
confidence: 99%
“…This finding is consistent with Khan et al . (2015), who emphasized that the negative and irregular temperature variations in case of the tomato-growing season could affect biomass accumulation. Tomato growth at low temperature resulted in lower number of flowers per cluster, number of fruits and yield per hectare as compared to plants produce in optimum temperature.…”
Section: Discussionmentioning
confidence: 99%